Market profiling of selected cosplayers in Metro Manila - Vergara, Veronica Jean G.
The increasing popularity and strong spending habits of the cosplay community makes them a valuable target for clothing-related business. This study created a market profile of selected cosplayers in Metro Manila according to their demographic and behavioral characteristics in cosplaying. It also identified possible market segments and suggested clothing-related businesses. One hundred forty one (141) cosplayers participated in the study. They were chosen through convenience and snowball sampling. Twenty (20) respondents were surveyed in a cosplay convention, while 121 respondents were surveyed online. The selected cosplayers were mostly females belonging to the youth group. They were students in between ages 13 to 25 years old and have low to medium monthly income or allowance. The respondents were willing to spend PhP 2,000.00 to 4,000.00 on average for cosplay costume. Market segments were identified based on the respondents' demographic characteristics such as age, gender, employment status, and monthly income or allowance, and behavioral characteristics such as cosplay character selection, cosplay motivation, cosplay costume acquisition, and costume usage. The clothing-related business identified were costume commissions, cosplay costume supplies and learning materials such as books and craft sets, cosplay-inspired casual clothes and cosplay workshop. A folow-up study with better sampling methods and a more comprehensive data regarding the behavior of cosplayers towards a perception of certain products is recommended to enhance the market profile.